New directions in social and cultural history - Handley, Sasha; McWilliam, Rohan; Noakes, Lucy (New directions in social and cultural history, 2018)
"What does it mean to be a social and cultural historian today? In the wake of the 'cultural turn', and in an age of digital and public history, what challenges and opportunities await historians in the early 21st century? In this exciting new text, leading historians reflect on key developments in their fields and argue for a range of 'new directions' in social and cultural history. Focusing on emerging areas of historical research such as the history of the emotions and environmental history, New Directions in Social and Cultural History is an invaluable guide to the current and future state of the field. The book is divided into three clear sections, each with an editorial introduction, and covering key thematic areas: histories of the human, the material world, and challenges and provocations. Each chapter in the collection provides an introduction to the key and recent developments in its specialist field, with their authors then moving on to argue for what they see as particularly important shifts and interventions in the theory and methodology and suggest future developments. New Directions in Social and Cultural History provides a comprehensive and insightful overview of this burgeoning field which will be important reading for all students and scholars of social and cultural history and historiography"--Provided by publisher.